Reactive power management at the transmission–distribution interface with the support of distributed generators – a grid planning approach. Issue 22 (16th November 2018) - Kraiczy, Markus; Wang, Haonan; Schmidt, Sebastian; Wirtz, Frank; Braun, Martin
Abstract : This study introduces a grid planning approach for reactive power management at the transmission–distribution interface with the support of distributed generators (DGs). The main research question is: can reactive power management with DGs provide controllable reactive power with a very high availability and can this reduce or avoid the demand for additional reactive power compensators in a distribution grid section (e.g. mechanically switched compensators)? Therefore, an availability analysis of reactive power support is performed for different generation types at the distribution level, like hydro, thermal, wind and photovoltaic power plants. For the investigated case study of a real German distribution grid, reactive power management with the support of DGs could relevantly reduce the demand for additional reactive power compensation devices. However, the effectivity of DGs for reactive power support strongly depends on the applied grid planning rules and requirements at the transmission–distribution interface.